1995
DOI: 10.1115/1.2835638
|View full text |Cite
|
Sign up to set email alerts
|

Darryl E. Metzger Memorial Session Paper: A Summary of the Cooled Turbine Blade Tip Heat Transfer and Film Effectiveness Investigations Performed by Dr. D. E. Metzger

Abstract: The clearance gap between the stationary outer air seal and blade tips of an axial turbine allows a clearance gap leakage flow to be driven through the gap by the pressure-to-suction side pressure difference. The presence of strong secondary flows on the pressure side of the airfoil tends to deliver air from the hottest regions of the mainstream to the clearance gap. The blade tip region, particularly near the trailing edge, is very difficult to cool adequately with blade internal coolant flow. In this case, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Yang and Diller [4] reported local heat transfer coefficients on a squealer tip experimentally, using a single point measurement on the cavity bottom. Kim et al [5] presented the results of Metzger's important experimental work, which showed the heat transfer and film cooling effectiveness with a rectangular tip model. Bunker and Bailey [6,7] experimentally investigated the heat transfer coefficient and leakage flow.…”
Section: Introductionmentioning
confidence: 98%
“…Yang and Diller [4] reported local heat transfer coefficients on a squealer tip experimentally, using a single point measurement on the cavity bottom. Kim et al [5] presented the results of Metzger's important experimental work, which showed the heat transfer and film cooling effectiveness with a rectangular tip model. Bunker and Bailey [6,7] experimentally investigated the heat transfer coefficient and leakage flow.…”
Section: Introductionmentioning
confidence: 98%
“…A review of the work done on tip-gap film cooling by Dr. Metzger's group is available in Kim et al (1995). More recently, Kwak and Han (2003a,b) and Christophel et al (2005) used thermal imaging techniques (Liquid crystal and IR thermography respectively) to measure detailed film cooling effectiveness contours on the tip with holes on the tip region of the pressure side and on the tip.…”
Section: Blade Tip Film Coolingmentioning
confidence: 99%